Background and activities of the Arctic Challenge for Sustainability (ArCS) project - Sueyoshi, Tetsuo; Fukasawa, Masao; Enomoto, Hiroyuki; Saitoh, Sei-Ichi; Kikuchi, Takashi (Polar Science, 2021)
This research note describes how the Japanese five-year Arctic research program “Arctic Challenge for Sustainability (ArCS)” was implemented, focusing on its activities that supported the research, with a brief introduction of the background of Japan’s Arctic research. There were two shifts in the style of Japan’s Arctic research during the last 10–15 years: from small research projects by individual scientists to a large national program, and from a purely scientific program to a comprehensive Arctic research program. Governmental policy played a crucial role in these shifts. As a national program, ArCS was required to expand Japanese Arctic research capabilities, and to deliver research results to multiple stakeholders. It was to meet these requirements that several supporting activities were included in addition to the research itself: establishing research and observation platforms, sending young researchers to overseas institutions, sending experts to the Arctic Council working groups, and enhancing outreach activities targeting both the general public in Japan and the international Arctic research community. Objectives, design, and outcomes of these supporting activities are described respectively. journal article